EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENGELUARAN KAS DENGAN APLIKASI SYSTEM APPLICATION AND PRODUCT IN DATA PROCESSING (SAP) DALAM RANGKA PENINGKATAN EFEKTIVITAS KINERJA (STUDI KASUS PADA SUBDIT TRESURI DAN PENGELOLAAN DANA PT. PELABUHAN INDONESIA III (PERSERO) KANTOR PUSAT) - Adesurya, Kris Maulana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Â The aim of this study is to evaluate the application of a cash expenditure accounting information system with SAP as conducted by the PT. Pelabuhan Indonesia III (Persero) Head Office, especially in the Sub-Directorate of Treasury and Fund Management, in order to improve performance effectiveness. This research is a qualitative study using a case study. Data was obtained by conducting observations, documentation, and interviews. The utilized analysis technique of this study was descriptive analysis by identifying the main components of the cash expenditure accounting information system, internal control of cash expenditure accounting information system, and comparing the theories with the practices that occur in the field. The results of the analysis showed that the implemented cash expenditure accounting information system with SAP had not been effective and efficient. This is seen in the incompatibility of internal controls in the division of tasks between cash functions and accounting functions. From the results of the analysis, it is recommended that the company implement strategies that can be used to improve the effectiveness of its performance.Keywords: Accounting information system, cash expenditure.Â Â